2015
DOI: 10.1097/sla.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Cost and Mortality Associated With Postoperative Acute Kidney Injury

Abstract: OBJECTIVE To determine the incremental hospital cost and mortality associated with the development of postoperative acute kidney injury (AKI) and with other associated postoperative complications. SUMMARY BACKGROUND DATA Each year 1.5 million patients develop a major complication after surgery. Postoperative AKI is one of the most common postoperative complications and is associated with an increase in hospital mortality and decreased survival for up to 15 years after surgery. METHODS In a single-center co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
263
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(282 citation statements)
references
References 35 publications
9
263
1
9
Order By: Relevance
“…13 Most studies that have explored the costs related to hospitalizations complicated by AKI have been single-center or local studies in specialized patient populations. 4,5,[14][15][16][17][18] Very few studies have used data after the year 2000, when the incidence of AKI began to increase, likely related to a combination of patient age, comorbidity burden, sepsis, heart failure, and nephrotoxic medications. 10,11 Moreover, it is unclear which patient and hospital characteristics contribute most to the cost of an AKI hospitalization, and how the costs of AKI compare to those for other acute medical conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Most studies that have explored the costs related to hospitalizations complicated by AKI have been single-center or local studies in specialized patient populations. 4,5,[14][15][16][17][18] Very few studies have used data after the year 2000, when the incidence of AKI began to increase, likely related to a combination of patient age, comorbidity burden, sepsis, heart failure, and nephrotoxic medications. 10,11 Moreover, it is unclear which patient and hospital characteristics contribute most to the cost of an AKI hospitalization, and how the costs of AKI compare to those for other acute medical conditions.…”
Section: Resultsmentioning
confidence: 99%
“…© Society of Hospital Medicine Acute kidney injury (AKI) is a common complication that affects as many as 20% of hospitalized patients, depending on the definition employed. [1][2][3] AKI is associated with significant morbidity and mortality; hospitalized patients with AKI require more investigations and medications, 4 develop more postoperative complications, 5 and spend more time in the intensive care unit than do patients without AKI. 6 Inhospital mortality for patients with AKI has recently been estimated between 20-25%, 3,7 and critically ill patients with AKI requiring dialysis experience mortality rates in excess of 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there is evidence surrounding the economic implications of post-operative AKI with significantly higher hospital cost in patients who develop AKI (18).…”
Section: Adverse Outcomes Following Post-operative Akimentioning
confidence: 99%
“…1,4,5 Acute kidney injury (AKI) is a common postoperative complication, and our group has shown that small changes in serum creatinine are associated with increased hospital and intensive care unit lengths of stay as well as hospital and ninety-day mortality rates after major surgery. [7][8][9][10] With the emergence of consensus criteria to standardize the definition of this postoperative complication, especially with mild and moderate degrees of AKI, recent studies within the vascular literature have demonstrated that AKI prevalence ranges from 13%-76% and is associated with adverse perioperative outcomes. [11][12][13][14] Many of these studies have focused on the prevalence of AKI after a specific procedure using small patient cohorts.…”
Section: Introductionmentioning
confidence: 99%